Unexpected consequences: women’s experiences of a self-hypnosis intervention to help with pain relief during labour - Finlayson, Kenneth; Downe, Soo; Hinder, Susan; Carr, Helen; Spiby, Helen; Whorwell, Peter (BioMed Central, 2015)
Background: Self-hypnosis is becoming increasingly popular as a means of labour pain management. Previous studies have produced mixed results. There are very few data on women’s views and experiences of using hypnosis in this context. As part of a randomized controlled trial of self-hypnosis for intra-partum pain relief (the SHIP Trial) we conducted qualitative interviews with women randomized to the intervention arm to explore their views and experiences of using self-hypnosis during labour and birth. Methods: Participants were randomly selected from the intervention arm of the study, which consisted of two antenatal self-hypnosis training sessions and a supporting CD that women were encouraged to listen to daily from 32 weeks gestation until the birth of their baby. Those who consented were interviewed in their own homes 8–12 weeks after birth. Following transcription, the interviews were analysed iteratively and emerging concepts were discussed amongst the authors to generate organizing themes. These were then used to develop a principal organizing metaphor or global theme, in a process known as thematic networks analysis. Results: Of the 343 women in the intervention group, 48 were invited to interview, and 16 were interviewed over a 12 month period from February 2012 to January 2013. Coding of the data and subsequent analysis revealed a global theme of ‘unexpected consequences’, supported by 5 organising themes, ‘calmness in a climate of fear’, ‘from sceptic to believer’, ‘finding my space’, ‘delays and disappointments’ and ‘personal preferences’. Most respondents reported positive experiences of self hypnosis and highlighted feelings of calmness, confidence and empowerment. They found the intervention to be beneficial and used a range of novel strategies to personalize their self-hypnosis practice. Occasionally women reported feeling frustrated or disappointed when their relaxed state was misinterpreted by midwives on admission or when their labour and birth experiences did not match their expectations. Conclusion: The women in this study generally appreciated antenatal self-hypnosis training and found it to be beneficial during labour and birth. The state of focused relaxation experienced by women using the technique needs to be recognized by providers if the intervention is to be implemented into the maternity service.